2012
DOI: 10.1021/ie3016973
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study of the Triboelectric Charging Behavior of Powders Using a Nonintrusive Approach

Abstract: Powder processing operations such as blending or pneumatic transport can potentially induce triboelectric charging with subsequent agglomeration. Traditionally the charging behavior is investigated using a Faraday cage. In this paper, an alternative nonintrusive probe connected to a voltmeter for comparative triboelectric charging studies of sieved pharmaceutically relevant materials such as α-lactose monohydrate (ALM) and adipic acid (AA) on acetal surfaces under controlled environmental conditions was explor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 52 publications
2
9
0
Order By: Relevance
“…This agreed with previous studies carried out by (Carter et al, 1992), (Eilbeck et al, 2000(Eilbeck et al, , 1999 and (Kwek et al, 2012) who showed the netcharge of lactose to increase with decreasing particle size. This could be explained as the specific surface area (per unit mass) increases with decreasing particle diameter and this makes a higher netcharge-to-surface ratio (net-CSR) for smaller particles obvious.…”
Section: Particle Size Distributionsupporting
confidence: 93%
“…This agreed with previous studies carried out by (Carter et al, 1992), (Eilbeck et al, 2000(Eilbeck et al, , 1999 and (Kwek et al, 2012) who showed the netcharge of lactose to increase with decreasing particle size. This could be explained as the specific surface area (per unit mass) increases with decreasing particle diameter and this makes a higher netcharge-to-surface ratio (net-CSR) for smaller particles obvious.…”
Section: Particle Size Distributionsupporting
confidence: 93%
“…6 is comparable to values obtained previously by Kwek et al 6 which ranged from 4.7 % to 32.7 % using a similar approach. For other techniques values in the range of 40-50 % up to 100 % have been reported.…”
Section: Verification Of Reproducibilitysupporting
confidence: 90%
“…6 However, preliminary tests with the coupled system revealed that a large number of factors may affect the overall electrostatic field and therefore calibration and optimisation are required.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations